Arousing the Sound: A Field Study on the Emotional Impact on Children of Arousing Sound Design and 3D Audio Spatialization in an Audio Story - Cuadrado, Francisco; Lopez-Cobo, Isabel; Mateos-Blanco, Tania; Tajadura-Jiménez, Ana (Frontiers in Psychology, 2020)
Sound from media increases the immersion of the audience in the story, adding credibility to the narration, but also generating emotions in the spectator. A study on 9-13 years-old children (N=253), using an audio story, investigated the emotional impact of arousal vs neutral treatment of sound and 3D vs stereo mix spatialization. The emotional impact was measured combining three different measures: physiological (Electrodermal activity), self-report (pre-post exposition), and richness of mental images elicited by the story (using Think-aloud technique after exposition). Results showed higher emotional impact of the arousal and 3D audio conditions, with different trends according to the age of the participants, and different types of interaction when both variables were combined.